PKM pemanfaatan akar dan tangkai kayu menjadi bonsai imitasi pada warga binaan Lapas Narkotika Bollangi - Ali Latif Amri; Muhammad Saleh Husain; Bakhrani A. Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The objectives of the Community Partnership Program (PKM) are Bollangi prison partner groups (partners) in theCommunity Partnership Program (PKM): (1) Provide counseling on the use of roots and stems of wood into imitation bonsai ofvarious models and forms, (2) Provide skills training design imitation bonsai from various roots and stems of various models andshapes, (3) Provide training on skills to clean the root bark and stalks into a framework of imitation bonsai of various models andshapes, (4) Provide training skills on shaping imitation bonsai from various roots and stalks of various models and shape, (5)Provide training in the skills to assemble flowers and plastic leaves on a wooden frame into imitation bonsai of various modelsand shapes, (6) Provide training skills in finishing imitation bonsai using a scratch-resistant melamine dico on a root frame andwooden stalk, (7) Provide information about imitation bonsai from the roots and stems of the wood can be marketed everywhere,(8) Providing counseling on the interest and motivation of artificial bonsai entrepreneurs from roots and stems of wood. Thetarget audience is a group of residents fostered by the narcotics prison Bollangi (partners). The method used in the delivery ofmaterial uses the lecture, discussion and question and answer method, while the application to students uses demonstrations.Expected target outcomes for Bollangi narcotics prison partners (partners) in the Community Partnership Program (PKM) are: (1)Can have knowledge of the use of roots and stems of wood into imitation bonsai of various models and shapes, (2) Can havebonsai design skills imitation of the roots and stems of various models and shapes, (3) Can have the skills to clean the root barkand stalks into a bonsai framework imitation of various models and shapes, (4) Can have the skill of forming imitation bonsai ofthe roots and stalks of various models and shapes , (5) Can have the skills to assemble flowers and plastic leaves on wood framesinto imitation bonsai of various models and shapes, (6) Can have the skills of finishing imitation bonsai work using scratchresistant melamine dico on the framework of roots and wooden stems, (7) Can have knowledge of imitation bonsai from the rootsand wooden stems which can be marketed everywhere, (8) Can have knowledge about the interests and motivations of imitationbonsai entrepreneurs from roots and wooden stems.